The arginine methyltransferase PRMT7 promotes extravasation of monocytes resulting in tissue injury in COPD - Günes Günsel, Gizem; Conlon, Thomas M; Jeridi, Aicha; Kim, Rinho; Ertüz, Zeynep; Lang, Niklas J; Ansari, Meshal; Novikova, Mariia; Jiang, Dongsheng; Strunz, Maximilian; Gaianova, Mariia; Hollauer, Christine; et al. (Nature communications, 2022)
Extravasation of monocytes into tissue and to the site of injury is a fundamental immunological process, which requires rapid responses via post translational modifications (PTM) of proteins. Protein arginine methyltransferase 7 (PRMT7) is an epigenetic factor that has the capacity to mono-methylate histones on arginine residues. Here we show that in chronic obstructive pulmonary disease (COPD) patients, PRMT7 expression is elevated in the lung tissue and localized to the macrophages. In mouse models of COPD, lung fibrosis and skin injury, reduced expression of PRMT7 associates with decreased recruitment of monocytes to the site of injury and hence less severe symptoms. Mechanistically, activation of NF-κB/RelA in monocytes induces PRMT7 transcription and consequential mono-methylation of histones at the regulatory elements of RAP1A, which leads to increased transcription of this gene that is responsible for adhesion and migration of monocytes. Persistent monocyte-derived macrophage accumulation leads to ALOX5 over-expression and accumulation of its metabolite LTB4, which triggers expression of ACSL4 a ferroptosis promoting gene in lung epithelial cells. Conclusively, inhibition of arginine mono-methylation might offer targeted intervention in monocyte-driven inflammatory conditions that lead to extensive tissue damage if left untreated.
Keywords: arginin; Animals; Arginine; Humans; histony; Histones; lidé; Protein-Arginine N-Methyltransferases; chronická obstrukční plicní nemoc; zvířata; Monocytes; Mice; Pulmonary Disease, Chronic Obstructive; monocyty; proteinarginin-N-methyltransferasy; intracelulární signální peptidy a proteiny; Intracellular Signaling Peptides and Proteins; myši